Subcapsular Sinus Macrophage Fragmentation and CD169(+) Bleb Acquisition by Closely Associated IL-17-Committed Innate-Like Lymphocytes - Gray, Elizabeth E. (Public Library of Science, 2012)
Subcapsular sinus macrophages (SSMs) in lymph nodes are rapidly exposed to antigens arriving in afferent lymph and have a role in their capture and display to B cells. In tissue sections SSMs exhibit long cellular processes and express high amounts of CD169. Here, we show that many of the cells present in lymph node cell suspensions that stain for CD169 are not macrophages but lymphocytes that have acquired SSM-derived membrane blebs. The CD169 bleb(+) lymphocytes are enriched for IL-17 committed IL-7Rα(hi)CCR6(+) T cells and NK cells. In addition, the CD169 staining detected on small numbers of CD11c(hi) dendritic cells is frequently associated with membrane blebs. Counter intuitively the CD169 bleb(+) lymphocytes are mostly CD4 and CD8 negative whereas many SSMs express CD4. In situ, many IL-7Rα(hi) cells are present at the subcapsular sinus and interfollicular regions and migrate in close association with CD169(+) macrophages. These findings suggest SSMs undergo fragmentation during tissue preparation and release blebs that are acquired by closely associated cells. They also suggest an intimate crosstalk between SSMs and IL-17 committed innate-like lymphocytes that may help provide early protection of the lymph node against lymph-borne invaders.